Inhibition of nitric oxide synthesis augments pulmonary oedema in isolated perfused rabbit lung. - Mundy, A; Dorrington, K (2000)
The role of nitric oxide (NO) in precipitating pulmonary oedema in acute lung injury remains unclear. We have investigated the mechanism of involvement of NO in the maintenance of liquid balance in the isolated rabbit lung. Thirty pairs of lungs were perfused with colloid for up to 6 h, during which pulmonary vascular resistance (PVR) and capillary pressure (PCP) were measured frequently, and time to gain 5 g in weight (t5) was recorded. Four protocols with different perfusate additives were studied: (i) none (control, n = 11); (ii) 10 mmol NG-nitro-L-arginine methyl ester (L-NAME) (n = 6); (iii) 10 mmol L-NAME with 100 mumol lodoxamide, an inhibitor of mast cell degranulation (n = 7); (iv) 10 mmol L-NAME with 10 mumol 8-bromo-3',5'-cyclic guanosine monophosphate (8Br-cGMP), an analogue of cGMP that may reduce vascular permeability by relaxing contractile elements in endothelial cells (n = 6). Neither PVR nor PCP differed between protocols. L-NAME markedly reduced t5 from 248 (27) min (mean (SEM)) in protocol (i) to 144 (5) min in protocol (ii) (P < 0.05). Both lodoxamide (t5 = 178 (7) min) and 8Br-cGMP (t5 = 204 (10) min) substantially corrected the effect of L-NAME (P < 0.005). Results suggest that maintenance of a low permeability by NO may involve mast cell stabilization and endothelial cell relaxation.